رمزية التجريد في الشعر الشعبي قصيدة "العصفور التائه" للدكتور عمرو خليفة النامي - جبران, رضا محمد (مجلة شروس العلمية, 2024)
Keywords: Ennami; Amr (1939-198X); Poésie – Djebel Nefousa

Ancient Infusen Poems (Part-I) - Buzakhar, Mazigh (Medium, 2024)
from 12th Century Manuscript ‘Siyar Wisyani’: Aẓil, the wise woman
Keywords: Poésie – Djebel Nefousa